Manajemen Strategi Sumber Daya Manusia dalam Pendidikan Islam untuk Penguatan Kompetensi, Kinerja, dan Profesionalisme Tenaga Pendidik - Neni Handayani; Ahmad Subagyo; Muhamad Sofian Hadi; Suharta (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
In 2020, the World Bank conducted a Service Delivery Indicator (SDI) survey to measure the performance and quality of education services. The survey was conducted in 263 schools under the auspices of the Ministry of Religious Affairs (Kemenag) and 87 elementary schools under the Ministry of Education and Culture. One of the results was the high level of teacher absenteeism in the basic education system in Indonesia, with almost one in four teachers (23.5 percent) absent from class on a given day. Most of these absences were officially permitted, indicating that the education management system needs to be improved. Human Resource Management (HR) in Islamic education has a strategic role in improving the quality of Islamic Educational Institutions (LPI). By referring to various theories of HR management, competence, performance, and professionalism, this study aims to analyze effective HR management strategies that can improve the quality of HR so that education services are also of high quality. Through a qualitative approach, data obtained from the analysis of various literatures, this study identifies various strategies that can be applied to achieve these goals. The results of the study indicate that training, development, and performance evaluation are key elements in effective HR management, in addition to the need for HR planning, compensation and rewards. It was also found that a holistic approach based on Islam can improve the effectiveness of human resource management in education, thus having a positive impact on the quality of educators (Ilhamsyah, 2024). This study also identified research gaps and novelties in the development of human resource management in Islamic educational institutions. Recommendations are given to stakeholders to develop more comprehensive policies in the management of Islamic educational human resources.